Effects of aging treatment on microstructure and mechanical properties of non-equiatomic high entropy alloy. (February 2023) - Zhou, Z.C.; Li, G.R.; Wang, H.M.; Zhou, P.J.; Dong, K.; Wei, Y.M.; Zhang, Z.B.; Dong, C.; Su, W.X.; Zhao, H.
Abstract: In this study, the cryogenically-processed FeCoNi1.5 CuB0.5 Y0.2 HEAs (high-entropy alloys) were subjected to aging treatment, such as different aging temperatures T (unaged sample, 700 °C, 750 °C, 800 °C), aging times t (unaged sample, 10 h, 12 h, 14 h) and the aging cycles N (unaged sample, one time, two times, three times). Under this condition, the changing laws of microstructure and mechanical properties of HEAs were explored. According to the experiment, with the increase of the aging temperature, the prolongation of the aging time or the growth of the number of aging cycles, the overall mechanical properties of the material have been significantly improved. In particular, when the aging conditions were T  = 750 °C, t  = 12 h, and N  = 2 times, the grain size of the optimized sample was reduced, and a large number of finely dispersed precipitates appeared, which can produce excellent strong-plastic synergy. Further analysis revealed that the complex interacting multi-component in the HEA constitute the heterogeneity level of the microstructure and also lead to effective multi-component strengthening. Especially in the samples after optimized aging parameters (DCAT 7), the activated back stress at boundaries of grains and the synergistic effect of nanoparticles and twins contribute to high strain hardening. In terms of micromechanical characteristics, the modulus of elasticity and nanohardness of each phase were obviously enhanced. In terms of macroscopic mechanical properties, Vickers hardness, compressive strength and maximum compression ratio also reached their maximum values, which were 53.4%, 19.6% and 43.5% higher than those of the single cryogenic sample, separately. Obviously, the overall strength-ductility has been improved simultaneously. Highlights: The properties of HEA were significantly improved after optimizing the aging parameters. Nanoparticles and twins help to increase both strength and ductility. The excellent mechanical properties of HEA are mainly attributed to multi-strengthening.